Research on Deformation Mechanisms of a High Geostress Soft Rock Roadway and Double-Shell Grouting Technology. (31st October 2021) - Wang, Fengnian; Chen, Shizhuang; Gao, Pan; Guo, Zhibiao; Tao, Zhigang
Abstract : In this study, the deformation characteristics and mechanical properties of coal and rock mass in the S2N5 working face of the Xiaokang coal mine are analyzed to address the problem of large deformation of soft rocks with high in situ stress surrounding roadways. Through a newly developed grouting pipe, a double-shell grouting technology, consisting of low-pressure grouting and high-pressure split grouting, is proposed for the Xiaokang coal mine. In addition, the effect of grouting is evaluated by borehole peeping and deformation monitoring. The results show that the double-shell grouting technology can effectively improve the overall mechanical properties of the surrounding coal and rock mass, preventing the large deformation and failure of the roadway. This technology can be useful when analyzing and preventing large deformation of soft rock roadways.